2021
DOI: 10.3389/fpsyg.2021.642590
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Feasibility of a Novel Virtual Reality-Based Intervention for Patients With Schizophrenia

Abstract: Schizophrenia is a severe and disabling mental illness, associated with persistent difficulties in social functioning. While gaining and retaining a job or staying socially integrated can be very difficult for the patients, the treatment of poor functionality remains challenging with limited options in pharmacotherapy. To address the limitations of medical treatment, several interesting and innovative approaches have been introduced in the field of psychotherapy. Recent approaches incorporate modern technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is also under study for treating schizophrenia. In a recent study, VR-based theory of mind intervention (VR-ToMIS), a novel method is explored, which enables patients to practice complex social interactions without the stress of real-life consequences (Vass et al, 2021). A case report showing promising results of VR-ToMIS was presented where a 50-year-old woman diagnosed with schizophrenia improved in ToM and communicative-pragmatic skills using VR-ToMIS (Vass et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also under study for treating schizophrenia. In a recent study, VR-based theory of mind intervention (VR-ToMIS), a novel method is explored, which enables patients to practice complex social interactions without the stress of real-life consequences (Vass et al, 2021). A case report showing promising results of VR-ToMIS was presented where a 50-year-old woman diagnosed with schizophrenia improved in ToM and communicative-pragmatic skills using VR-ToMIS (Vass et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, VR-based theory of mind intervention (VR-ToMIS), a novel method is explored, which enables patients to practice complex social interactions without the stress of real-life consequences (Vass et al, 2021). A case report showing promising results of VR-ToMIS was presented where a 50-year-old woman diagnosed with schizophrenia improved in ToM and communicative-pragmatic skills using VR-ToMIS (Vass et al, 2021). There is another study that developed a cognitive-behavioral treatment (CBT) supported by VR that has shown its utility and effectiveness in the treatment of adjustment disorder (Quero et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, VR established itself as a means of investigating threat perception, fear, and exposure processing (Glotzbach-Schoon et al, 2013;Shiban et al, 2013;Diemer et al, 2015). In recent years, research has been extended to other mental disorders such as major depressive disorder, bipolar disorder, and schizophrenia (Chen et al, 2021;Vass et al, 2021). This body of research has concluded that VR is a valuable tool for assessing the presence of symptoms in valid and controlled settings (Rus-Calafell et al, 2018;Browning et al, 2020;Fernández-Sotos et al, 2020;Hørlyck et al, 2021).…”
Section: Introductionmentioning
confidence: 99%